Improving production and prediction of the flow regimes, pressure drop, and void fraction in the perforated horizontal wellbore - Kareem H.J.; Hasini H.; Abdulwahid M.A. (Elsevier Ltd, 2024)
This study aimed to investigate how oil production could be improved by experimenting with different distribution methods across multiple profiles. The authors tested five different profiles that included uniform radial airflow (explained in profile 1) and variable radial airflow (explained in profiles 2, 3, 4 and 5) in a perforated horizontal wellbore. In addition, the study predicted the behavior of total pressure drop, superficial mixture velocity and void fraction encountered in different flow patterns (bubble, slug, stratum and stratum wave flow). Flow patterns were predicted using ANSYS Fluent R3 with a borehole length of 3 m and an ID of 0.0381 m. This was designed with 12 perforations opening vertically at the wellbore with a phase angle of 180 and a perforation density of 4 shots per foot to simulate the complex flow in a horizontal wellbore. In the perforated section, there was a fluctuation in the behavior of the parameters, while in the non-perforated section, the behavior remained constant. The behavior of the total pressure drop, the superficial velocity mixtures and the void fraction were also reasonably uniform in profile 1 in the perforated section. In contrast, they were irregular in the other profiles. In profiles 2, 3, 4 and 5, the behavior of the mixture superficial velocity and void fraction was inverse to the total pressure drop. Note that all theoretically calculated pressure drop modes increased as the Reynolds number of the mixture increased. The liquid and air product increased with increasing Reynolds number of mixture flow in the profiles. In contrast, in profile 1, lower production was obtained through all flow patterns due to the influence of the mixture pressure and the friction factor. The Vogels method was used to calculate maximum production from the horizontal wellbore. The convergence between experimental and numerical results was good during all cases (flow patterns), with some difference in the static pressure drop behaviuor occurring during flow patterns (bubble, dispersed bubble and slug flow). 2023 Elsevier B.V.